Ultra‐Broadband High‐Efficiency Airy Optical Beams Generated with All‐Silicon Metasurfaces. Issue 1 (29th October 2020) - Ju, Zezhao; Wen, Jing; Shi, Lina; Yu, Binbin; Deng, Ming; Zhang, Dawei; Hao, Weiming; Wang, Jian; Chen, Shuqi; Chen, Lin
Abstract: Conventional approaches for generating Airy beams rely upon bulky and costly systems, which impede the miniaturization of optical systems. Metasurfaces have provided a compact method to generate Airy optical beams, but the current schemes suffer from the issues of narrow bandwidths and/or low transmission efficiencies. Here, a design strategy of constructing broadband and high‐efficiency transmissive Airy optical beam generator by taking advantages of the high birefringence and transmission efficiency of dielectric metasurfaces is proposed. The local amplitude and phase of transmitted light can be simultaneously modulated to satisfy the Airy function by controlling the orientation angles of silicon nano‐pillars, regardless of the incidence wavelength. The resultant Airy beam generator is experimentally verified within an ultra‐wide operation bandwidth from 1.1 to 1.7 µ m. The remarkable diffraction‐free, self‐accelerating, and self‐healing properties of Airy beams are also demonstrated. The results may power up viable opportunities for practical devices and applications of metasurface‐based Airy beams. Abstract : The local amplitude and phase of transmitted light can be simultaneously modulated to satisfy the Airy function by controlling the orientation angles of silicon metasurfaces, regardless of the incidence wavelength. The Airy optical beams enabled by silicon metasurfaces are experimentally observed within an ultra‐wide operation bandwidth from 1.1 to 1.7 µm.